The Development of Serious Game to Teach the Concept of Dunya and Akhirah to Young Muslims - Haris Setyawan; Reza Giga Isnanda; Elvan Diano; Muhammad Fadlun Subarkah (Universitas Muhammadiyah Yogyakarta, 2020)
Nowadays, young Muslims are so busy with their needs in Dunya (this World) that they overlook the importance of preparing for life in Akhirah (the Hereafter). Afterall, one of the teaching in Islam is to prioritize the Akhirah than the Dunya. Because of the lack of awareness, many young Muslims neglect their religious duties such as Sholat or reciting al-Qur’an. To help introduce, teach, and remind them the concept of balancing life in Dunya and Akhirah, a solution that can pique their interest is a necessity. Therefore, this paper explain the development process of serious game to teach the concept of Dunya and Akhirah. The game implements the main mission and hidden mission that resemble Dunya and Akhirah responsibility respectively. The game’s effectivity was then evaluated with pre-test and post-test method. The result suggested that the game can increase the player’s knowledge in Dua and awareness in Dunya and Akhirah. This shows the potential of the game as learning media.